Investigating the expression and functional activities of the proteins that are involved in uterine fluid pH regulation at different stages of the oestrous cycle and in steroid replaced ovariectomized rats / Khadijeh Gholami - Gholami, Khadijeh (2013)
Precise control of the uterine luminal fluid pH is important for a number of key reproductive events. We hypothesized that sex-steroid could participate in this control via affecting the expression of H+ and HCO3- transporters as well as the enzyme that is involved in their generation. In view of this, we investigate the expressions and functional activities of few membrane transporters including CFTR, SLC26A6, NBC and NHE as well as CA enzyme in the uterus. Adult female WKY rats were divided into two main groups; (i) ovariectomized, steroid-replaced and (ii) intact rats at different phases of the oestrous cycle. The level of mRNA, the expression and distribution of proteins as well as the functional involvement of these transporters /enzyme were investigated. Our functional studies revealed that estrogen caused an increase in the pH, volume, Cl-, HCO3- and Na+ content of this fluid while progesterone resulted in vice versa. The effects of estrogen were antagonized by glibenclamide (CFTR inhibitor), DIDS (anion-exchanger inhibitor) and acetazolamide (CA inhibitor) while progesterone effects were inhibited by acetazolamide and EIPA (NHE inhibitor). A similar increase in the pH, volume, HCO3-, Cl- and Na+ content were observed during estrus and proestrus stages, which were inhibited by glibenclamide, DIDS and acetazolamide. Meanwhile, acetazolamide and EIPA antagonized the reduction in pH, volume, Cl-, HCO3- and Na+ concentrations during diestrus. The mRNA and protein expression of CFTR, SLC26A6 and NBC were increased following estrogen treatment while P treatment resulted in a decrease in these transporters expression. While NHE1 expression was up-regulated by P, NHE2 and NHE4 expressions were up-regulated by estrogen. Meanwhile, CAII and XII expressions were both stimulated by estrogen and progesterone although progesterone treatment resulted in a lower expression of CA enzyme as compared to estrogen. A similar effect was observed at different phases of the oestrous cycle, during which the pH and volume of the fluid were both increased. This was associated with an increase in the expressions of CFTR, NBC and SLC26A6. At metestrus and diestrus however, an increased in NHE1 expression together with the reduction in CFTR, NBC and SLC26A6 could result in the lower luminal fluid pH and volume. Immunohistochemistry findings indicated that CFTR and SLC26A6 were expressed at the apical membrane, while NBC was bilaterally expressed with a higher intensity at the basolateral membrane under the estrogen effect and at estrus. NHE isoforms expression revealed bilateral localization of this protein’s isoforms with NHE1 distributed mainly on the apical membrane under the influence of progesterone and during diestrus while NHE2 and NHE4 were distributed mainly at the basolateral membrane under estrogen influence and at estrus. CA II was expressed exclusively in the glandular epithelia while CAXII was expressed at both the glandular and endometrial epithelia. In conclusion, the differential expression of these transporters/ enzyme by sex-steroids and at different phases of the oestrous cycle may explain the changes in the uterine fluid pH under these different conditions.